2022
DOI: 10.1097/cji.0000000000000440
|View full text |Cite
|
Sign up to set email alerts
|

A Single Center Retrospective Study of the Impact of COVID-19 Infection on Immune-related Adverse Events in Cancer Patients Receiving Immune Checkpoint Inhibitors

Abstract: Immune checkpoint inhibitors (ICIs) can cause a variety of immune-related adverse events (irAEs). The coronavirus disease 2019 (COVID-19) is associated with increased amounts of pro-inflammatory cytokines, which may affect the outcome of irAEs. Data are limited regarding the impact of COVID-19 on irAEs in ICI-treated cancer patients. Hence, in this study, we retrospectively analyzed ICI-treated adult patients with malignant solid tumors at a single institution between August 2020 and August 2021. Patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Histological findings of EMB shows infiltration of CD4- and CD8-positive lymphocytes in myocardial tissue, as well as CD68-positive macrophages in patients with severe clinical symptoms, such as fulminant myocarditis ( 20 , 21 ). There are reports that the SARS-CoV-2 genome was detected in myocardial tissue from some COVID-19 patients ( 22 25 ). However, there have been reports of virus-negative COVID-19-associated myocarditis, and the authenticity of the SARS-CoV-2 genome remains uncertain ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Histological findings of EMB shows infiltration of CD4- and CD8-positive lymphocytes in myocardial tissue, as well as CD68-positive macrophages in patients with severe clinical symptoms, such as fulminant myocarditis ( 20 , 21 ). There are reports that the SARS-CoV-2 genome was detected in myocardial tissue from some COVID-19 patients ( 22 25 ). However, there have been reports of virus-negative COVID-19-associated myocarditis, and the authenticity of the SARS-CoV-2 genome remains uncertain ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previous studies have yielded conflicting results. For example, Mengni Guo et al reported that COVID-19 infection may pose a risk of severe irAEs in cancer patients receiving ICIs [ 24 ]. On the other hand, a registry for thoracic cancers did not find a significant impact of ICIs on COVID-19 outcomes [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that COVID-19 vaccines are safe for cancer patients receiving anti-PD-1 treatment and that ICIs do not worsen outcomes in cancer patients with COVID-19 [ 18 – 22 ]. Some studies have evaluated the safety and efficacy of ICIs in lung cancer patients with COVID-19 infection [ 23 , 24 ]. The Omicron variant has presented a new challenge to Chinese healthcare systems and care of cancer patients due to its persistent spread in the end of 2022.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ICI immune-mediated lung injury and COVID-19 have overlapping features and common clinical and radiological manifestations, making it not only difficult to distinguish between the two but also impossible to exclude a negative synergistic effect of both on lung injury [ 77 ]. Taken together, clinicians need to be more cautious with ICI-treated cancer patients during COVID-19.…”
Section: Interaction Between Icis and Sars-cov-2 Infectionmentioning
confidence: 99%